The effect of neurofeedback on the quality of life of patients with tinnitus referred to the Isfahan hearing aid center - Hashemi Jazi, Seyed Mostafa; Nilforoush, Mohammad Hossein; Amin, Zahra (Researcher Bulletin of Medical Sciences, 2019)
Tinnitus is one of the common and chronic problems of the ear and nose. It has various causes and in spite of various treatments, it decreases the quality of life of patients. Neurofeedback is a method that has been providing observation and recording of brain waves and it is effective in controlling brain activity and self-awareness in various diseases such as depression, hyperactivity and tinnitus, and etc. The aim of this study was to evaluate the effect of neurofeedback on improving the quality of life of patients with tinnitus referring to Isfahan Auditory Center. Methods: The Iranian version of the quality of life questionnaire, which is presented by the WHO, was given to patients with tinnitus who referred to Isfahan Auditory Center for treatment of neurofeedback. The questionnaires were completed by the patients before starting treatment and again after the completion of the course. During the study, people aged 20-70 years without psychotics and echoes of pathologic and etiologic causes were included in the study. The scores were calculated based on QOL questionnaire and, with other demographic information, and entered into the SPSS software for analysis. Results: Thirty-five patients were enrolled in the study. The mean of ages was 37.28 ± 11.20 years, 48.57% were male and 51.43% were female. Eleven patients (31.42%) have one-way tinnitus. Ten patients were ill for less than 6 months and 11 patients were ill over 2 years, and in 18 patients (51.42%), hearing loss was observed. The mean QOL score in patients, before treatment, was 74.8, and it was 99 after treatment; so, there was 32.33% increase in scores. This increase was significant (p <0.01). However, there is no significant relationship between gender, age and duration of the disease with improving quality of life (p >0.05). There is only a significant relationship between the number of treatment sessions and the improvement of quality of life (p <0.05) and increased QOL rate by 25.31%. Conclusion: Finally, it can be concluded that tinnitus has a significant effect on the quality of life of patients, and the neurofeedback has been able to increase the quality of life of patients, but this relationship is not related to gender, age, and other variables except the number of treatment sessions.